COX-2 Overexpression in Schneiderian Papillomas - Jeffrey D. Suh MD; Kevin Hur MD; Elisabeth H. Ference MD, MPH; David D. Lam BS; Andrew Fong MD; Adrian J. Correa MD; Bozena Wrobel MD (Allergy & Rhinology, 2020)
Background Schneiderian papillomas (SP) are aggressive sinonasal tumors that occasionally extend into areas that are surgically unresectable. Objective evaluate the signifcance of cyclo-oxygenase-2 (COX-2) expression in SP. Methods Immunohistochemistry for COX-2 was performed on SP samples and middle turbinates from chronic rhinosinusitis without nasal polyps controls obtained during surgical resection between 2009–2017. A positive stain was defined as having 10% or more cells exhibiting diffuse immunoreactivity. Comparisons were performed using Fisher Exact tests, t-tests, and ANOVA. Results The study included 67 tumor samples and 9 controls from two academic institutions. The mean age of the SP group was 55.4 years and 53.2 years in the control group (p = 0.71). Thirty-nine (58.2%) SP patients had previous surgery compared to 1 (11.1%) in the control group (p = 0.01). The most common tumor attachment sites were the maxillary (47.8%) and ethmoid (25.4%) sinuses. Fifteen (22.4%) SP samples stained strongly positive for COX-2 and 24 (35.8%) stained weakly positive compared to no positive stains in the control group (p < 0.01). When stratified by COX-2 intensity, there were no statistically significant differences in gender, smoking history, history of previous sinus surgery, site of attachment, papilloma subtype, or future recurrence between SP samples. Conclusion COX-2 was overexpressed in 58.2% of SP cases, and strongly positive in 22.4% of cases, compared to no positive staining among controls. No significant differences in COX-2 expression were observed between SP subtypes or recurrent tumors. Further studies are warranted to evaluate COX-2 as a possible therapeutic target in tumors that overexpress the enzyme.